Proximate Analysis And Growth Performance Of Local Upland Rice (Oriza Sativa. L) Treated With Various Doses Of Fish Waste–Secondary Vegetation Bokashi On Marginal Lands Of Small Islands - Wa Ode Hinarti; Anshar; Samsibar (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Rice (Oryza sativa L.) is an essential food crop and a primary staple for most Indonesian people. One of the potential rice types that can be developed in small island regions is local upland rice, which is known for its strong adaptability to marginal soils and drought conditions. This study aimed to determine the effect of various doses of fish-waste and secondary-vegetation bokashi on the growth of two local upland rice cultivars, Paewuna (Muna Island) and Wakawondu (Buton Island). The research was conducted in Lupia Village, Kabangka Subdistrict, Muna Regency, from July to October 2025. A factorial randomized block design (RBD) was used, consisting of four bokashi doses: without bokashi (P0), 10 ton ha⁻¹, 20 ton ha⁻¹, and 30 ton ha⁻¹, combined with two cultivars: Wakawondu and Paewuna. Growth parameters observed included plant height, number of tillers, number of leaves, leaf length, and leaf width at 4, 6, and 8 weeks after planting (WAP). The results of the study showed that the application of bokashi had a highly significant effect on plant height and leaf length of local upland rice at 4 and 6 weeks after planting (WAP), and on leaf width at 8 WAP, but had no significant effect on plant height at 8 WAP, tiller number at 4 WAP, and the number of leaves at 4, 6, and 8 WAP. The application of 20 tons ha⁻¹ bokashi produced the best plant growth. Furthermore, the effect of cultivar differences showed that the cultivars had a highly significant effect on plant height and leaf length at 4, 6, and 8 WAP, tiller number at 4 WAP, and the number of leaves at 4 and 6 WAP, and a significant effect on tiller number at 6 WAP. The Paewuna cultivar demonstrated superior growth performance compared to the Wakawondu cultivar. Proximate analysis indicated that both Wakawondu and Paewuna cultivars contain high nutritional value, with carbohydrate content ranging from 24–29%, protein 6–8%, fat 1–2%, and crude fiber 8–9%, and are categorized as good for consumption as a community food source.